THE EFFECTIVENESS OF FACEBOOK ADVERTISING ON CONSUMER PURCHASE INTENTION ON MILLENNIAL GENERATION IN MANADO - Yudhatama Indrawan; Joy Elly Tulung; Fitty Valdi Arie (Universitas Sam Ratulangi, 2022)
The purpose of this research is to analyze the influence of Attitude, Ability to recall, and frequency of clicking online advertisement on purchase intention of millennial generation in Manado. This research used a quantitative method. 100 samples were collected with questionnaires distributed via social media from the millennial generation in Manado. Multiple linear regression and 5 points Likert scale was used to help the data analysis in this research. The conclusion of this study was (1) partially a positive and significant relationship between the independent variable (attitude towards an online ad) on purchase intention and (2) partially a positive and not significant relationship between the independent variable (ability to recall an online ad) on purchase intention (3) partially a positive and significant relationship between the independent variable (frequency of clicking an online ad) on purchase intention. The result of this research shows that attitude towards online ads(X1) ability to recall online ads(X2) and frequency of clicking online ads (X3) have a positive and significant correlation with purchase intention(Y) partially.